Improvement of mechanisms for ensuring the stability of the financial and credit system in the implementation of issues of sustainable development of the economy of the Republic of Kazakhstan - Abilkasym, A.B.; Rysbayeva, S.K.; Zhadigerova, G.A.; Alieva, F.U.; Aitzhanov, T.A. (BUKETOV BUSINESS REVIEW, 2023)
Object: This article is devoted to the study of ensuring the financial and credit system in the implementation of issues of sustainable development of the economy of the Republic of Kazakhstan. Ensuring the financial stability of the Republic of Kazakhstan should be based on value-oriented, risk-oriented approaches and, above all, on a systematic approach. Methods: The paper uses content analysis of modern sources, comparative and logical analysis, generalization, statistical analysis of the dynamics of indicators. Findings: The functionality of the proposed mechanism largely depends on the quality of corporate ethics and the depth of its implementation in the activities of credit institutions. Thus, fraudulent actions provoked by a business entity (credit institution), including deliberate actions, create a crisis situation in the country, from which the mechanism cannot refuse. The proposed system is able to manage only real threats to financial stability, namely those caused by objective internal or external factors. Conclusions: Financial stability is vital for improving the mechanisms for ensuring the stability of the financial and credit system, since most transactions in the real sector of the economy are carried out through the financial system. The importance of implementing the issues of sustainable development of the economy of the Republic of Kazakhstan is perhaps most obvious in situations of financial instability.